Socio-ecological resilience and language dynamics: An adaptive cycle model of long-term language change. Issue 1 (3rd September 2018) - Hudson, Mark J
Abstract: Language is thought to be a crucial element behind Pleistocene expansions of Homo sapiens but our understanding of language change over the very long term is still poor. There have been two main approaches to language dynamics in this context. One assumes a continual ebb and flow of local human populations and languages, leading to high levels of 'patchiness' in both genes and languages. Another approach argues that long-term equilibrium leads not to patchiness but to areal diffusion and convergence. Both of these approaches assume equilibrium to be the norm. However, research in ecology since the 1970s has found that ecosystems have multiple potential states rather than a single equilibrium point. Under the name of resilience theory, such thinking is being increasingly applied to coupled socio-ecological systems using the concept of the adaptive cycle. This article proposes a model of long-term language change based on the adaptive cycle of resilience theory.